An investigation of 2D viscous model for high speed laminar flow application - Mohd Khairi bin Md Yassin (2023)
This thesis reports the investigation made using FORTRAN lanugage. The investigation focused on the two-dimensional condensing flow in converging-diverging nozzles which is the Binnie and wood nozzle.